Efficacy and safety of an Albuvirtide-based regimen for preventing mother-to-child transmission of multidrug-resistant HIV: a case report - Na Li; Shifei Wen; Fangfang Zhu; Guirong Liu; Daqing Zhu (BMC Pregnancy and Childbirth)
Abstract Background Antiretroviral drugs are essential for preventing mother-to-child transmission (MTCT) of HIV in HIV-infected pregnant women. However, ART treatment for HIV-infected pregnant women with multidrug resistance remains a major challenge. Effective and safe ART regimens for preventing MTCT should be tailored to this special population. Albuvirtide (ABT) is along-acting fusion inhibitor with proven efficacy and safety in adults with multidrug-resistant HIV. Herein, for the first time, we report the use of an ABT-based ART regimen in pregnant women infected with multidrug-resistant HIV. Case presentation A 25-year-old female HIV patient with an estimated gestational age of 14 weeks who received the TDF + 3TC + EFV regimen. The tests revealed an HIV- RNA concentration of 1730 copies/mL, a CD4 T lymphocyte (CD4 cell) concentration of 145 cells/µL and genotypic resistance to NRTI and NNRTI. The patient showed a decreased viral load (30 copies/mL) and increased CD4 cells (215 cells/µL) after 12 weeks of ABT + 3TC/DTG treatment. Her physical condition was good, and no drug- related adverse reactions occurred. By the prenatal period (40 weeks), HIV RNA became undetectable, and CD4 cells had risen to 348 cells/µL. Finally, the patient delivered a healthy female baby who was negative for HIV, and the follow-up showed normal growth. Conclusions In our case, ABT-based antiretroviral regimen was effective in suppressing viral load (VL) in pregnancy, and there is no reported safety issues for the mother or the baby. Albuvirtide use in pregnancy might represent a strategy to avoid in utero transmission of MDR-HIV, but further investigation is warranted.